The SAGE handbook of regression analysis and causal inference - Best, Henning 1975-; Wolf, Christof (SAGE Reference, 2015)
This handbook presents a collection of introductory materials on finite state theories and their applications. It offers an open treatment of the types of algorithms and data structures that are typically retained quietly by companies and provides performance information regarding individual techniques for various domain areas. A complete reference on finite state-based models and their applications, the book can be used by beginners as a quick reference guide and by researchers for an in-depth study of this areaEstimation techniques : ordinary least squares and maximum likelihood / Martin Elff -- Bayesian estimation of regression models / Susumu Shikano -- Linear regression / Christof Wolf, Henning Best -- Regression analysis : assumptions and diagnostics / Bart Meuleman, Geert Loosveldt, Viktor Emonds -- Non-linear and non-additive effects in linear regression / Henning Lohmann -- The multilevel regression model / Joop Hox, Leoniek Wijngaards-de Meij -- Logistic regression / Henning Best, Christof Wolf -- Regression models for nominal and ordinal outcomes / J. Scott Long -- Graphical display of regression results / Gerrit Bauer -- Regression with complex samples / Steven G. Heeringa, Brady T. West, Patricia A. Berglund -- Matching estimators for treatment effects / Markus Gangl -- Instrumental variables regression / Christopher Muller, Christopher Winship, Stephen L. Morgan -- Regression discontinuity designs in social sciences / David S. Lee, Thomas Lemieux -- Fixed-effects panel regression / Josef Bruderl, Volker Ludwig -- Event history analysis / Hans-Peter Blossfeld, Gwendolin J. Blossfeld -- Time-series cross-section / Jessica Fortin-Rittberger.